ReFocus. The films of William Castle - Leeder, Murray, 1982- (Edinburgh : Edinburgh University Press Ltd, 2018)
With an influence felt on directors like Joe Dante, Robert Zemeckis and John Waters, this volume reappraises Castle's legacy as an innovator as much as a showman.
1. When Strangers Marry: Film Noir as Mediated Gothic / Hugh S. Manon -- 2. Gender in William Castle's Westerns / Zack Rearick -- 3. He Earned Our Forgiveness: William Castle and American Movie Showmanship / A.T. McKenna -- 4. Collective Screams: William Castle and the Gimmick Film / Murray Leeder -- 5. Ghost Show Ballyhoo: Castle's Macabre Will Scare You to Death / Beth Kattelman -- 6. How to View 13 Ghosts / Eliot Bessette -- 7. Chaos Made Flesh: Mr. Sardonicus (1961) and the Mask as Transformative Device / Alexandra Heller-Nicholas -- 8. A Sick Mind in Search of a Monstrous Body: William Castle and the Emergence of Psychological Horror in the 1960s / Steffen Hantke -- 9. "What a Wicked Game to Play?" Playfulness, Generic Hybridity, and Cult Appeal in Castle's 1960s Films / Caroline Langhorst -- 10. "Where Did Our Love Go?" The Case of William Castle's The Night Walker / Michael Pelitti -- 11.H omo/cidal: William Castle's 1960s Killer Queers / Peter Marra -- 12. The Cinematic Pandemonium of William Castle and John Waters / Kate J. Russell.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Castle, William -- Criticism and interpretation; Castle, William; PERFORMING ARTS -- Reference; LITERARY CRITICISM -- Feminist; Motion picture producers and directors; United States; Criticism, interpretation, etc